2012
DOI: 10.1002/anie.201206873
|View full text |Cite
|
Sign up to set email alerts
|

Back Cover: Two Interconvertible Structures that Explain the Spectroscopic Properties of the Oxygen‐Evolving Complex of Photosystem II in the S2 State (Angew. Chem. Int. Ed. 39/2012)

Abstract: The structural flexibility … show that the core of the photosynthetic oxygen-evolving complex exists in two interconvertible structures with distinct spectroscopic properties. This solves the puzzle of the two interconvertible signals in the S 2 oxidation state of the catalyst, and paves the way for a deeper understanding of its function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 0 publications
5
20
0
Order By: Relevance
“…Thus the structure 1a(R) may be a plausible model for the S 1 state in accord with theoretical conclusions by several groups. [42][43][44][45][46][47][48][49][50][51][52][53][54] However, present UB3LYP calculations by the use of basis set I have shown that the 1b(C) structure is more stable by 0.9 (2.2) kcal mol −1 than the 1a(R) structure without (with) ZPE. The corresponding energy difference obtained by basis set II becomes 1.9 (3.1) kcal mol −1 .…”
Section: The Optimized Geometries Of Camn(iii) 3 Mn(iv)o 4 (Oh)(h 2 Omentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the structure 1a(R) may be a plausible model for the S 1 state in accord with theoretical conclusions by several groups. [42][43][44][45][46][47][48][49][50][51][52][53][54] However, present UB3LYP calculations by the use of basis set I have shown that the 1b(C) structure is more stable by 0.9 (2.2) kcal mol −1 than the 1a(R) structure without (with) ZPE. The corresponding energy difference obtained by basis set II becomes 1.9 (3.1) kcal mol −1 .…”
Section: The Optimized Geometries Of Camn(iii) 3 Mn(iv)o 4 (Oh)(h 2 Omentioning
confidence: 99%
“…[5][6][7][8][9] The computational results [42][43][44][45][46][47][48][49][50][51][52][53][54] have revealed possible geometrical structures of the CaMn 4 O 5 cluster, suggesting contaminations of reduced structures such as the S −3 structure 51 in the new XRD structure; details of recent debates [42][43][44][45][46][47][48][49][50][51][52][53][54] are given in the ESI. † Nevertheless the high-resolution XRD experiment 27,28 has elucidated, for the first time, hydrogen bonding networks that confine the CaMn 4 O 5 cluster in the OEC of PSII.…”
Section: Introductionmentioning
confidence: 99%
“…This work has opened the way for corroborating the chemical and physical details of OEC with use of electronic structure simulation as well as spectroscopic analysis. Earlier computational studies on the Mn 4 CaO 5 have been done entirely within the mean‐field electronic structure approaches on the basis of density functional theory (DFT) …”
Section: Applicationsmentioning
confidence: 99%
“…Photosynthetic water-splitting reaction is catalyzed in nature by Mn 4 CaO 5 cofactor embedded within the oxygen-evolving complex (OEC) in photosystem II. [214,215] Determination of the exact molecular details of the biological water-splitting reaction has been a challenging task for computational [153], [216][217][218][219][220][221] and experimental [214,215,[222][223][224][225][226][227][228][229][230][231] studies of the OEC. The molecular-level understanding of this reaction should inspire us with the basic design of efficient synthetic catalysts using abundant metals, as found in OEC.…”
Section: Entangled Valence Many-electron Wave Function Of Mn 4 Cao 5 mentioning
confidence: 99%
See 1 more Smart Citation